329 EFFECTS OF A 12-WEEK RISK FACTOR REDUCTION PROGRAM IN OVERWEIGHT CHILDREN AND ADOLESCENTS WITH METABOLIC SYNDROME. (1st January 2006) - Luna, C.F; Evans, W. N.; Mayman, G. A.; Acherman, R. J.; Kip, K. T.; Cass, K. A.; Rothman, A.; Gustafson, A.; Lowe, A.; Coviello, L.; Restrepo, H.
Abstract : Background: Metabolic syndrome (MS) is a recognized risk factor for diabetes and cardiovascular disease in adults and occurs in up to 29% of US obese children and adolescents. Although the long-term consequences of the MS in childhood are unknown, early intervention to promote healthy changes in lifestyle may have a beneficial effect in the factors used a diagnostic criteria of MS. Objectives: To assess the effect of a 12-week medically supervised program of nutritional counseling and exercise on each diagnostic criterion of MS in a group of overweight children with this diagnosis. Methods: This study included 31 children and adolescents, with body mass index (BMI) ≥ 95th percentile, who met the diagnostic criteria for MS as defined by NANHES III. The difference in the mean value of each diagnostic criterion was analyzed using paired t -test. Results: There were 12 females and 19 males with a mean age of 11.4 years (range: 8-15 years), and a mean BMI Z-score of 2.33 ± 0.33. The ethnic composition was Hispanic: 74%, Caucasian: 16% and other races: 10%. Comparison of mean values is shown in the table below. Conclusion: A 12-week intervention program to encourage healthy nutritional and exercise patterns in this group of overweight children and adolescents with MS was associated with significant improvement in the mean values of triglycerides and HDL cholesterol levels.